2021
DOI: 10.30773/pi.2021.0343
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Adverse Childhood Experiences on Offspring’s Internalizing and Externalizing Problems

Abstract: Objective Adverse childhood experiences (ACEs) are associated with negative physical and mental health outcomes across the lifespan, but research on intergenerational transmission of maternal ACEs and its impact on the offspring’s mental health problems are limited. The study examines the effects of maternal ACEs on the risk of internalizing or externalizing problems among offspring.Methods There were 450 mother-child dyads. Mothers completed the Adverse Childhood Experiences Questionnaire. The child outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…However, little attention has focused on how parents' childhood experiences, adverse or positive, can in uence cross-generational transmission. Interestingly, a body of studies on the intergenerational effect of maternal childhood trauma revealed a marked negative impact on their children's triggering behavioral problems such as socio-emotional symptoms, depression, anxiety, internalizing, externalizing and total problems (Cooke et al, 2019;kang et al, 2021;Roubinov et al, 2022;Russotti et al, 2021). Here, our results are in agreement with previous data, demonstrating that children of mothers who suffered childhood trauma are at greater risk of externalizing, internalizing and total problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little attention has focused on how parents' childhood experiences, adverse or positive, can in uence cross-generational transmission. Interestingly, a body of studies on the intergenerational effect of maternal childhood trauma revealed a marked negative impact on their children's triggering behavioral problems such as socio-emotional symptoms, depression, anxiety, internalizing, externalizing and total problems (Cooke et al, 2019;kang et al, 2021;Roubinov et al, 2022;Russotti et al, 2021). Here, our results are in agreement with previous data, demonstrating that children of mothers who suffered childhood trauma are at greater risk of externalizing, internalizing and total problems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies address the need for a broader investigation of potential mechanisms that explains the maternal childhood trauma impact across generations (Cooke et al, 2019;kang et al, 2021;Roubinov et al, 2022). An important objective is to understand why some children are at risk of developing behavioral problems in response to maternal childhood trauma, while others are not.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of ACE DOHaD-like programming of later-life NCDs include: asthma [12], obesity and diabetes [13], cardiovascular disease [14], neurobehavioral disorders [15], and cancer [16]. Furthermore, beyond the scope of this present review, ACEs can transmit elevated intergenerational risk for chronic disorders across generations [17,18]. The CDC developed an ACE pyramid to visually reflect the diverse outcomes of ACEs across the lifespan [19].…”
Section: Adverse Childhood Experiences and The Microimmunosomementioning
confidence: 99%
“…Examples of ACE DOHaD-like programming of later-life NCDs include: asthma [12], obesity and diabetes [13], cardiovascular disease [14], neurobehavioral disorders [15 ], and cancer [16]. Furthermore, beyond the scope of this present review, ACEs can transmit elevated intergenerational risk for chronic disorders across generations [17,18]. The U.S. Center for Disease Control and Prevention (CDC) developed an ACE pyramid to visually reflect the diverse outcomes of ACEs across the lifespan [19].…”
Section: Adverse Childhood Experiences and The Microimmunosomementioning
confidence: 99%